Mamey Sapote Growing in the Florida Home Landscape - Carlos F. Balerdi; Jonathan H. Crane; Ian Maguire (EDIS, 2006)
Revised! FC30, a 10-page fact sheet by Carlos F. Balerdi, Jonathan H. Crane, and Ian Maguire, provides homeowners with a basic reference for growing canistel in the home landscape. Tables include characteristics and cultivars, cultural practices by month, fertilizer program and nutritional values. Published by the UF Department of Horticultural Sciences, September 2005.